Research on Collision Detection Algorithm of Dual Manipulator - Jianchun Liu; Kun Qin; Yanfeng Lin; Zian Liu (Jixie chuandong)
In order to ensure the safety of dual manipulator in public space， an accurate and efficient collision detection algorithm is proposed. The sphere and capsule bounding boxes are used to simplify the manipulator model， and the collision is judged according to the intersection between the bounding boxes. The second projection method is used to achieve fast detection. The bounding box is projected into line segments. If the projection line segments are not overlapped， the bounding box will not intersect. If the projection line segments are overlapped， the problem is further transformed into the shortest distance solution from point to point， point to line and line to line. Through the analysis of the simulation software and physical manipulator experimental platform， the results show that the algorithm has high detection efficiency and can be directly implanted into the manipulator controller program， meet the safety requirements.